PENGARUH STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL (DAR) PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Windi Novianti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
ABSTRAKThis study is performed to examine The effect of Asset Structure and Growth of Sales to Capital Structure at Property and Real Estate companies listed in Indonesia Stock Exchange (IDX) period 2012-2016.The objective of this study is to analyze the effect of the statistical variable to capital structure (debt to asset ratio)The method used is descriptive and verification with quantitative approach. The samples is used as an object of study as many as six (6) companies and panel data used by 30 panels of data. While the data used is secondary data including the data of financial statements and balance sheets. The test statistic used is multiple linear regression analysis, the classical assumption test, correlation analysis, coefficient of determination and hypothesis testing are calculated using Eviews 7.0 for Windows.This research results in partial effect, asset structure and sales growth gives significantly positive effect on capital structure (debt to asset ratio). Asset structure and sales growth givessimultaneously gave the influence to capital structure (debt to asset ratio) about56,7958%, where as the remaining 43,2042 % was influenced by another variable.Keywords: Asset Structure, Sales growth and Capital structure (Debt to Asset ratio)